Studi Komparasi Hermeneutika Negosiasi Ibnu Rusyd dan Khaled untuk Mengatasi Ketimpangan Penafsiran - Firdaus, Yusuf; Hidayah, Alfa Handi (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2024)
The phenomenon of Qur'anic interpretation is increasingly haphazard, especially in the highly disruptive 21st century. Although the Qur'an is open to be understood by anyone, we must criticize the ideology of the reader as an interpreter to investigate the subjectivity of interpretation. Through a comparative study of the negotiation hermeneutics of Ibn Rushd and Khaled Abou el-Fadl, this article aims to direct the interpreter to a progressive quasi-objectivist typology, which suppresses the subjectivity of interpretation and recontextualization according to the times to get out of the rigidity of understanding. This study aims to compare the negotiation hermeneutics of Ibn Rushd and Khaled Abou el-Fadl through Paul Ricoeur's meta-hermeneutic approach. By using a descriptive qualitative method, this study explores the similarities, differences, and relevance of the two figures' hermeneutics in the contemporary context. The results show that this integrative approach is effective in revisiting the negotiation hermeneutics of the two figures to complement the study of Qur'anic hermeneutics, offering practical contributions to the balance of interpretation, as well as looking at the phenomenon of interpreters and audiences that occur in Indonesia. Practically, this article emphasizes the urgency of moral-based interpretation and transparency, creating harmonization between interpreters and audiences. Academically, this research offers a more inclusive ideology of hermeneutical balance of negotiation through the development of al-Qur'anic hermeneutic discourse in critical-ideological aspects while explaining its relevance to the needs of Indonesian people in this contemporary century.